Blood pressure elevation response to radiofrequency energy delivery: one novel predictive marker to long-term success of renal denervation. Issue 12 (December 2018) - Xu, Yanping; Xiao, Peilin; Fan, Jinqi; Chen, Weijie; Du, Huaan; Ling, Zhiyu; Liu, Zengzhang; Su, Li; Woo, Kamsang; Yin, Yuehui
Abstract : Background: Previous studies showed that radiofrequency energy delivery of the renal artery could induce an immediate and substantial blood pressure (BP)-elevation response, which might be indicative of the increase in central sympathetic nervous activity. Objective: The current study was to investigate whether the presence of BP-elevation response to radiofrequency energy delivery can serve as a surrogate to predict BP reduction following renal artery sympathetic denervation (RDN). Method: Data were collected on 67 patients undergoing RDN for drug-resistant hypertension. The BP-elevation response to radiofrequency application was defined as elevation of SBP by at least 10 mmHg during radiofrequency energy delivery. The extent of BP reduction at 1, 3, 6, 12 months after RDN were analyzed. Multivariable linear regression analysis of baseline and procedural characteristics was performed to identify the determinants of BP reduction after RDN. Results: Ten patients (14.9%) were classified as nonresponders to radiofrequency delivery and showed significantly lower BP reduction compared with responders. The SBP reductions of radiofrequency delivery responders vs. nonresponders were 31.2 ± 8.6 vs. 11.4 ± 8.6 mmHg, 36.3 ± 10.0 vs. 14.6 ± 10.6 mmHg, 39.9 ± 9.9 vs. 15.2 ± 8.8 mmHg, and 40.0 ± 8.7/13.5 ± 5.8 mmHg ( P  < 0.001 for all) at 1, 3, 6, and 12 months, respectively. On multiple linear regression analysis, higher baseline office SBP, the presence of BP-elevation response to radiofrequency energy delivery, and especially larger number of BP-elevation response points, were independent predictors of SBP reduction at 6-month and 12-month follow-up. Conclusion: Baseline SBP and BP-elevation response during radiofrequency ablation, as well as larger positive response points to radiofrequency energy delivery could be an effective intraprocedural predictive markers to long-term procedural success of RDN.